Persepsi dan Preferensi Mahasiswa Universitas Tazkia Terhadap Penggunaan Alat Pembayaran Non-Tunai dalam Transaksi Sehari-hari (Studi Kasus: E-Wallet dan QRIS) - Habib, Muhammad; Al Muhajjir, Fais (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to explore the perceptions and preferences of Tazkia University students regarding the use of non-cash payment methods, particularly e-wallets and the Quick Response Code Indonesian Standard (QRIS), in daily transactions. Using a qualitative approach with a case study design, data were collected through semi-structured in-depth interviews with 35 student participants. Data were analyzed using thematic analysis to identify patterns in perceptions and preferences. The findings indicate that students have positive perceptions of the convenience and efficiency of QRIS and e-wallets, but they express concerns about security issues, data privacy, and compatibility with Islamic values such as transaction permissibility (halal) and avoiding riba. Their primary preference is e-wallets due to integration with daily applications and cashback promotions, whereas QRIS is more favored for transactions with small merchants and MSMEs around campus. Islamic ethical factors emerged as significant moderators, where students prioritized platforms compliant with Sharia principles, such as those partnered with Islamic banks. This study fills a research gap in the context of Islamic universities in Indonesia, where religious values uniquely influence the adoption of financial technologies. Practical implications include recommendations for universities to enhance literacy in Sharia-based digital payments and collaborate with fintech providers to obtain halal certification.